2013
DOI: 10.1089/jpm.2012.0307
|View full text |Cite
|
Sign up to set email alerts
|

Personal Dignity in the Terminally Ill from the Perspective of Caregivers: A Survey among Trained Volunteers and Physicians

Abstract: Background: Although dignity is increasingly considered a goal of palliative care, little research has evaluated the understanding of dignity at the end of life from a caregiver's perspective. Objective: The study objective was to investigate and compare the views of trained volunteers and SCEN physicians on maintaining dignity for patients reaching the end of life. Design: The study is a survey questionnaire study. Subjects: Subjects were two groups of caregivers involved in care for dying patients: trained v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The PDI is a novel screening instrument tapping into multiple sources of distress salient for patients with limited life expectancies[ 17 ]. The PDI has been validated in multiple languages and applied in various palliative care settings and studies worldwide [ 18 24 ]. One national study reported that amongst patients with varying stages of cancer, the PDI readily helped clinicians identify dignity related distress.…”
Section: Introductionmentioning
confidence: 99%
“…The PDI is a novel screening instrument tapping into multiple sources of distress salient for patients with limited life expectancies[ 17 ]. The PDI has been validated in multiple languages and applied in various palliative care settings and studies worldwide [ 18 24 ]. One national study reported that amongst patients with varying stages of cancer, the PDI readily helped clinicians identify dignity related distress.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the PDI was found to be helpful in showing that physicians tend to have a limited vision of dignity, wherein they consider the physical aspects of suffering most influential in preserving dignity, whereas caregivers tend to underline the significant role of psychosocial aspects in preserving dignity at the end of life. 10 Given the importance of preserving dignity in health care systems, the PDI has been translated and validated in several countries to test its role from a cross-cultural perspective. Studies carried out in Italy, 11 Germany, 12 The Netherlands, 13 and Spain 14 have shown the PDI to have good psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Both were concerned with physical as well as psychosocial aspects influencing dignity. Earlier research in other contexts showed that physicians mainly focussed on physical aspects of suffering and less on psychosocial aspects [ 23 , 24 ]. The way in which the Dutch nursing home system is organized, i.e.…”
Section: Discussionmentioning
confidence: 99%